The pollination and scent ecology of selected Cape milkweeds (Apocynaceae: Asclepiadoideae) - Chirango, Yolanda Tendai (Department of Biological Sciences, 2017)
Milkweeds (Asclepiadoideae, Apocynaceae) possess a complex floral morphology that has made them prime candidates for investigating the evolution of plant-pollinator relationships. In South Africa, the pollination ecology of this diverse group has largely been focused in the summer rainfall region. This study focused on Western Cape species in the winter and summer-winter rainfall transition zones. The aim was to determine the pollinators of the study species and assess, describe and quantify their floral attractants. Thus offering a basis of comparison with the previously studied summer rainfall species. The pollination systems of seven milkweed species occurring in the Western Cape were investigated by determining floral visitors and several floral traits that may act as attractants of these visitors. For each study species an attempt at pollinator observations was carried out in several sites across the Cape; floral scent samples were collected through headspace sampling and analysed using GC-MS (gas chromatography-mass spectrometry); floral colour was analysed using spectral reflectance measurements; and nectar was measured to quantify floral rewards. Some Cape milkweeds displayed a more generalized pollination system compared to their summer rainfall congeners. A diverse range of visitors were observed on two Gomphocarpus species, Gomphocarpus cancellatus and G. filiformis in the Fynbos and Succulent Karoo biomes respectively, in contrast to their summer rainfall congeners, which are exclusively wasp pollinated or much less generalized. These two Gomphocarpus species offered floral visitors nectar as a reward with a concentration of 53% in G. cancellatus and a lower 15% in G. filiformis. The species emitted very different scents, G. cancellatus produced a scent dominated by irregular terpenes while G. filiformis scent largely consisted of benzenoid compounds. Although visited by a variety of different insect families and lesser-double collared sunbirds, honeybees and Balbyter ants were found to be the most efficient at removing pollinaria from G. cancellatus and G. filiformis respectively. Eustegia minuta, a Cape endemic, is almost exclusively pollinated by bibionid flies. This is the first record of the pollinators for this monotypic genus, as well as the first for the tribe Eustegieae. Additionally, this study is the first record of a milkweed-bibionid pollination system. The flowers produced very low nectar volumes, displayed minimal visual cues but produced a strong pungent odour dominated by an unidentified compound. This strong scent is thought to play an important role in attracting bibionids while also deterring other potential visitors. The scent profiles of four other previously unstudied Cape milkweeds, namely Cynanchum obtusifolium, C. zeyheri, Fockea capensis and Secamone alpinii were also analysed and shown to be mainly dominated by monoterpenes and benzenoids. Their scent profiles differed markedly from each other as well as to their congeners. The presence of skatole in S. alpinii suggests that it may attract coprophagic flies, small Nematoceran flies were observed drinking nectar from its flowers. While F. capensis produced scent associated with moths. Further observations are needed to confirm true pollinators for both species. The two Cynanchum species produced scent that was very different to each other as well as their congeners. Cynanchum obtusifolium is known to be bee pollinated however its scent profile did not align with this. While C. zeyheri produced a benzenoid-dominated scent with compounds associated with moths. Scent appears to be the most prominent pollinator attractant in the study species compared to floral colour. The concentration and volume of nectar rewards may also be significant. The structural complexity of the flowers is suggestive of a strong floral filter in some species (e.g. Eustegia minuta). Morphologically similar species were found to employ vastly different floral chemical strategies to attract but possibly also deter and filter out floral visitors. The Cape milkweeds therefore offer many opportunities for further pollination studies.